Diens en diensbaarheid tot opbou van die kerk - Barnard, A. C. (Verbum et ecclesia, 1988)
Service and Servitude in View of the Edification of the Church The most important change Christ brings about is that people who, in the past, desired to be served, are now willing to serve. The believer is a person who serves and the church is a service community. The service is comprehensive: we serve God, we serve our fellow believers, we serve in the church, we serve in the world, we serve people when they are in need, wherever they are, and we serve God in our services of worship.